Proposals for additional forms of saving for retirement in Poland - Agnieszka Pobłocka (Economic and Environmental Studies (E&ES), 2017)
In order to secure the retirement some Poles decided to save under the third pillar. This article presents proposals for additional forms of saving for retirement in the form of Employee or Personal Equity Plans proposed in the Strategy for Responsible Development - Capital Construction Programme published by the Ministry of Development in July 2016. The study presents the form of voluntary savings under the third pillar and presents an analysis based on modelling of the replacement rate for a proposed rate of return on investment and the annual rate of wage growth.
Keywords: J32; J14; 330; retirement provision; sample forms of additional savings; Employee Capital Plans; Individual Plans Capital; the replacement rate